Molecular Characteristics and Pathogemcity Of The Infectious Bursal Disease Virus Isolated In Malaysia - Rachmat, Roosevien Farida Nilawati (2006)
Infectious bursa1 disease (IBD) is an acute viral disease of young chicken and causes serious treat in poultry industry worldwide due to high mortality and immunosuppression. The disease is caused by IBD virus (IBDV), which belongs to the genus Avibirnavirus of family Birnaviridae. Two distinct serotypes of IBDV are serotype 1 and 2. Serotype 1 is pathogenic to chicken and classified as the classical (ca), very virulent (vv) and variant (va) IBDV. The objectives of this study were to isolate, identify, characterise and determine the pathogenicity of IBDV isolated in Malaysia. IBDV isolates namely UPM03 11 and UPM03292 were obtained from field IBD outbreaks in Selangor in 2003. The IBDV isolates were inoculated in specific pathogen free (SPF) embryonated chicken eggs and resulted 100% embryonic mortality within day 3 post inoculation (pi). Acute severe necrotising bursitis was observed in SPF chicken inoculated with the IBDV isolates. The IBDV was detected in lymphoid cells of bursa of Fabricius using immunoperoxidase staining (IPS).The hypervariable region of VP2 gene of UPM0311 and UPM03292 was amplified by reverse transcriptase polymerase chain reaction (RT-PCR). The sequence were aligned, analysed and subjected to restriction fragment length polymorphism (RFLP). A phylogenetic tree was constructed. The study showed that the UPM0311 and UPM03292 isolates were characterised as wIBDV and caIBDV, respectively. The nucleotide sequence of UPM03292 and UPM0311 IBDV isolates were submitted to Genbank with the accession number of DQ074690 and DQ074691, respectively. The UPM03 1 1 shared the same amino acid molecular marker for vvIBDV at positions 222(A), 242(1), 253(Q), 256(1), 284(A) and 294(I) of the hypervariable region of VP2. Meanwhile UPM03292 has amino acid substitutions at (A222P), (1242V), (1256V), and (1294L) and unique for caIBDV. The nucleotide sequence for UPM0311 and UPM03292 IBDV isolates were successfully cut by restriction enzyme at BspM, Ssp I, Sty I, Tag I and BstNI, SyI, Sad, MboI, respectively. UPM03 1 1 showed highest homologous similarity in nucleotide and amino acid to the reported Malaysian wIBDV. However, UPM03292 have identical with caIBDV STC and highest similarity with classical hot vaccine (Bursavac). The phylogenetic tree showed that the UPM03292 IBDV isolate located in the same group of the caIBDV and formed subranch with American caIBDV (STC) and American classical hot vaccine (Bursavac). Meanwhile UPM03 11 IBDV isolate was group together with vvIBDV and has shared a common evolutionary origin with other Malaysian wIBDV. The UPM0311 was inoculated into 28-day-old SPF chickens to determine the response of the bursa of Fabricius, bone marrow and blood to the VVIBDV. The chickens were inoculated with the virus titer of 106.2 EIDso via oral route. The chickens were sacrificed at various intervals through 14 days of the trial period. Samples of blood, bone marrow and bursa of Fabricius were collected, processed, examined and analysed. The study showed that the pack cell volume (PVC) and thrombocyte decreased at 2 to 5 days pi. In contrast, the basophil, heterophil, monocyte and lymphocytes were increased at 4 to 12 hours, 3 hours to 2 days, 12 hours to 2 days and 15 minutes to 12 hours pi, respectively. However, the total lymphocyte count was decreased at 1 day to 14 pi. Overall leukocyte was increased at 6 to 12 hours and decreased at 3 to 14 days pi. Histologically, acute moderate to severe cellular degeneration and necrosis were observed in bone marrow at day 2 to 5 pi, but the organ recovered at the late stage of infection. Severe acute necrotising bursitis was recorded at day 2 to 5 pi, whilst at the later stage of infection severe chronic bursitis with severe follicular atrophy was observed. By using immunoperoxidase staining (IPS), the virus was detected in the blood, bone marrow and bursa of Fabricius at 6 hours to 5 days pi, 3 to 5 days pi and 1 to 10 days pi, respectively.